The immunoproteasome‐specific inhibitor ONX 0914 reverses susceptibility to acute viral myocarditis. Issue 2 (2nd January 2018) - Althof, Nadine; Goetzke, Carl Christoph; Kespohl, Meike; Voss, Karolin; Heuser, Arnd; Pinkert, Sandra; Kaya, Ziya; Klingel, Karin; Beling, Antje
Abstract: Severe heart pathology upon virus infection is closely associated with the immunological equipment of the host. Since there is no specific treatment available, current research focuses on identifying new drug targets to positively modulate predisposing immune factors. Utilizing a murine model with high susceptibility to coxsackievirus B3‐induced myocarditis, this study describes ONX 0914—an immunoproteasome‐specific inhibitor—as highly protective during severe heart disease. Represented by reduced heart infiltration of monocytes/macrophages and diminished organ damage, ONX 0914 treatment reversed fulminant pathology. Virus‐induced immune response features like overwhelming pro‐inflammatory cytokine and chemokine production as well as a progressive loss of lymphocytes all being reminiscent of a sepsis‐like disease course were prevented by ONX 0914. Although the viral burden was only minimally affected in highly susceptible mice, resulting maintenance of immune homeostasis improved the cardiac output, and saved animals from severe illness as well as high mortality. Altogether, this could make ONX 0914 a potent drug for the treatment of severe virus‐mediated inflammation of the heart and might rank immunoproteasome inhibitors among drugs for preventing pathogen‐induced immunopathology. Synopsis: Resembling disease course in patients pre‐disposed for severe pathogen‐induced cardiac pathology, A/J mice exhibit high susceptibility for virus‐induced adverse immune response activation. Systemic application of the LMP7‐specific immunoproteasome inhibitor ONX 0914 inversed this hereditary predisposition. Vehicle‐treated A/J mice develop a fulminant myocarditis with large foci of inflammatory lesions and disturbances of diastolic filling, leading to low cardiac output and high mortality. Systemic immunoproteasome inhibition in mice utilized by application of the LMP7‐specific proteasome inhibitor ONX 0914 mediates systemic and local suppression of pro‐inflammatory cytokine/chemokine production. Destructive inflammation of the heart muscle, and therefore immunopathologically‐induced organ damage are significantly reduced. Although the viral burden is only minimally affected, the resulting maintenance of immune homeostasis ensures a stable cardiac output and significantly increases survival upon virus encounter. Pathogen‐directed adaptive immunity in terms of antibody production and establishment of virus‐specific memory status is maintained or even improved. Abstract : Resembling disease course in patients pre‐disposed for severe pathogen‐induced cardiac pathology, A/J mice exhibit high susceptibility for virus‐induced adverse immune response activation. Systemic application of the LMP7‐specific immunoproteasome inhibitor ONX 0914 inversed this hereditary predisposition.